Effects of Conditioning Temperature on Pellet Quality of Nursery Pig Diets - G. E. Nichols; C. R. Stark; A. M. Ogles; K. M. Dunmire; C. B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2019)
The objective of this experiment was to determine the effect of conditioning temperature on pellet durability index (PDI) and pellet hardness. A phase 1 swine nursery diet was formulated to contain 25% spray-dried whey. The diet was manufactured and pelleted at the Kansas State University O.H. Kruse Feed Technology and Innovation Center, Manhattan, KS. The treatments consisted of three different conditioning temperatures: 130, 145, and 160°F. Diets were steam conditioned (10 in width × 55 in length Wenger twin staff pre-conditioner, Model 150) for approximately 30 sec on a 1-ton 30-horsepower pellet mill (1012-2 HD Master Model, California Pellet Mill) with a 3/16 in × 1 1/4 in pellet die (L:D 6.7). Treatments were pelleted at 3 separate time points to provide 3 replicates per treatment. Samples were collected directly after discharging from the pellet mill and cooled in an experimental counterflow cooler. Samples were analyzed for PDI using the Holmen NHP 100 (TekPro Ltd, Norfolk, UK) in duplicate for each replicate. Pellet hardness was determined by evaluating the peak amount of force applied before the first signs of fracture. Pellets were crushed perpendicular to their longitudinal axis using a texture analyzer. A total of 30 pellets of similar length were selected at random from each replication to be tested and the force needed to crush each pellet was averaged within replication. Although conditioning temperature was increased in a linear fashion, a quadratic increase (P<0.002) in hot pellet temperature was observed. Increasing conditioning temperature resulted in increased (linear,P<0.045) PDI and pellet hardness. There was a tendency for a low correlation (P<0.076,r= 0.618, r2= 0.382) between pellet hardness and PDI. Overall, increasing the conditioning temperature increased both pellet hardness and pellet durability; however, these two responses were not strongly correlated. Future research and more data need to be generated to determine the relationship between PDI and pellet hardness at varying levels of pellet quality to determine what factors influence this relationship.
Keywords: Pellet Quality; Pellet Hardness; Conditioning Temperature